Baryon Lagrangians in Chiral Perturbation Theory - Papageorgiou,Paris Nikolas (2025)
We construct the meson-baryon chiral Lagrangian at orders two and three. The Lagrangian is constructed in the three-flavour case and with scalar, pseudoscalar, vector and axial-vector external sources included. We discuss the basic ideas of ChPT and the relations that are used to minimise the chiral Lagrangian. The relations that were used are the Bianchi identity, the Cayley-Hamilton relation, the Schouten identity, the meson and meson-baryon LO equations of motion, the total derivative relation and two anti-symmetry equations. The construction and minimisation of the chiral Lagrangian were performed using the programming languages FORM and C++, respectively.
Keywords: Chiral Perturbation Theory; ChPT